Crossing takeover premiums and mix of payment: An empirical test of contractual setting in M&A transactions - de La Bruslerie, Hubert (Journal of Banking & Finance, 2013)
The analyses of the tender offer premiums and of the means of payment should not be performed separately. In the empirical literature, these two variables are often considered independently, although they may have an endogenous relationship in a contractual setting. Using a sample of European M&As over the 2000–2010 decade, we show that these two variables are jointly set in a contractual empirical approach. The relationship between the percentage of cash and the offer premium is positive: higher premiums yield payments with more cash. We highlight that the payment choice is not a continuum between full cash and full share payments. Two different regimes of payment in M&A transactions are empirically characterized. We analyze the major determinants of M&A terms when the offer premium and the means of payment are jointly set. The underlying rationale of an asymmetry of information and a risk-sharing calculus is found to be significant in the setting of the agreement.